Experimental assessment of the discharge characteristics of multi-type retired lithium-ion batteries in parallel for echelon utilization. (15th November 2022) - Chang, Long; Ma, Chen; Zhang, Yulong; Li, Hongyu; Xiao, Linjing
Abstract: The large-scale retired lithium-ion batteries (LIBs) from electric vehicles provide considerable social, economic, and environmental benefits in echelon utilization compared to the immediate recycling. However, the diversity of retired LIBs in chemistry, packaging, energy density, and manufacturer make it hard to screen and sort for the echelon utilization. Therefore, from a new perspective of parallel configuration, this paper assesses the discharge characteristics of multi-type retired lithium-ion batteries to obtain the screening and regrouping criteria for improving utilization. Firstly, we experimentally study the discharge current and state of charge distributions of different type of packs with retired cells in parallel. According to the results, the mathematical relationship between cell-to-cell parameter and current distribution within parallel-connected cells is unraveled, and find that the slop of open circuit voltage and the product of cell resistance and capacity are the key factors for the inhomogeneities. To further improve utilization of various retired cells, we connect cells with different packing and chemistry in parallel. Results demonstrate that the cells with the same chemistry can be connected in parallel even with different packing and energy density. For the different chemistry, the parallel manner is suitable for combining NMC and NCA, however, not for LMO and NCA. Finally, compared with the traditional methods, the proposed regrouping methodology is validated based on a case study to ensure continuing safety and improve utilization, and find the consistency of resistance is more important than that of capacity for retired cells in parallel. Highlights: The diversity among retired lithium-ion batteries is systematically summarized. Discharge characteristics of the parallel-connected multi-type cells are studied. Correlations between key factors and inhomogeneities are unraveled. A novel regrouping methodology for retired cells is proposed and validated.